Приближенный анализ одной пространственной, конвективной задачи теплопроводности - Шевченко, А.И.; Миненко, А.С. (Видавничий дім "Академперіодика" НАН України, 2007)
The problem of three-dimensional stationary convection in the liquid phase is investigated. A method of studying this problem by means of the expansion in a small Reynolds number is proposed. In this case, the zero and first expansion terms are defined by the Ritz method. A formula of the dependence of the free-boundary equation on the Reynolds number is obtained.